2022
DOI: 10.7759/cureus.25571
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Outcomes of Infants Born to Mothers With Active COVID-19 Infection

Abstract: IntroductionCOVID-19, caused by SARS-CoV-2, is a highly contagious respiratory tract infection. A major concern of SARS-CoV-2 infection in pregnant women is vertical maternal-fetal transmission and the ramifications on infant hearing. This retrospective study aims to investigate whether perinatal exposure to SARS-CoV-2 has an impact on the hearing of the offspring. MaterialsThe study population included neonates born to unvaccinated COVID-19 positive mothers in the University Hospital of Patras, Greece from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…Similar to our ndings, most studies published during the covid-19 pandemic do not support strong evidence of auditory system insult due to intrauterine infection by the SARS-CoV-2 virus mirrored on normal newborn hearing screening tests [14,[37][38][39][40][41]. However, other studies are showing a possible negative impact on hearing of newborns of mothers infected by covid-19 during pregnancy [15,16].…”
Section: Discussionsupporting
confidence: 63%
“…Similar to our ndings, most studies published during the covid-19 pandemic do not support strong evidence of auditory system insult due to intrauterine infection by the SARS-CoV-2 virus mirrored on normal newborn hearing screening tests [14,[37][38][39][40][41]. However, other studies are showing a possible negative impact on hearing of newborns of mothers infected by covid-19 during pregnancy [15,16].…”
Section: Discussionsupporting
confidence: 63%
“…They observed no statistically significant difference between cases and controls. Kosmidou et al [ 21 ] reported that 21.87% of neonates failed the first screening while all these neonates cleared the second screening. A study by Tanyeri Toker et al reported no significant association between COVID-19 infection during different trimesters and congenital hearing loss.…”
Section: Discussionmentioning
confidence: 99%